Pemahaman Keagamaan (Tekstualis dan Kontekstualis, Inklusif Dan Ekslusif) - Ansori; Mutya Istikarani; Lisariyadi; Kasful Anwar (PT. Hasba Edukasi Mandiri, 2025)
This paper examines two main approaches to understanding religion, namely the textualist approach that emphasizes the literal meaning of religious texts, and the contextualist approach that considers the historical and social background in interpreting teachings. In addition, it also discusses the differences between an inclusive attitude, which is open to religious plurality and upholds interfaith dialogue, and an exclusive attitude that emphasizes a single truth and tends to reject outside views. This study aims to provide a comprehensive picture of the dynamics of religious understanding, as well as to encourage a more balanced, tolerant, and contributive approach in the life of a pluralistic society. An open and reflective understanding is expected to be the foundation for creating social harmony and harmony between religious communities. The main focus of this study is to understand how textual or contextual orientation influences a person's religious attitude, and how this understanding develops into inclusiveness or exclusivity in socio-religious life.